Profiles of political leaders at the local government level - Legaspi, Perla E. (CLCD research report, 2005)
"Dr. Perla E. Legaspi's "Profiles of Political Leadership at the Local Government Level" focuses on two municipal mayors, two city mayors, and two provincial governors. It sought to identify characteristics and leadership styles of local leaders and explain why they are effective and transformational leaders. The results of her study were disseminated in a seminar where there were free and open discussions on her findings."--Preface.